Exchange rate misalignment and economic growth: recent evidence in Malaysia - Niaz Ahmad, Mohd Naseem; M. S., Hamizah (Universiti Putra Malaysia Press, 2013)
The present study aims at investigating the growth effects of real exchange rate misalignments in Malaysia over the period 1991:1-2009:4. The RER misalignment is built through the estimation of the NATREX equilibrium model. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach to cointegration framework, the results indicate the presence of positive and significant relationship between the RER misalignment and economic growth. This finding obtained is consistent with the notion that the RER misalignment through the distortion in relative price has systematic influence on the pattern of economic development.